Prevention of light pollution - Baneen Jameel Jabr Hasoon; Mohammed Salman Mohsen Salman; Osama Emad kadim Jasem; Jaafar Hussein Ali Ramid (Genius Journals, 2024)
In this paper, we touched on light pollution and demonstrated ways to prevent it, as the huge amount of lights used at night in cities and human and industrial clusters has become a source of environmental, health and scientific concern. Years ago, the term “light pollution” was called “light pollution”, which is one of the new forms of factors that cause harm to organisms. Living creatures represent an increasing source of nuisance to ecosystems, in addition to their bad impact on human health due to some human activities. Anyone who observes satellite images taken at night may not have missed the spread of sparkling lights, the glow of which varies depending on the region in most parts of the land. Although they indicate the size of Human activity and industrial and civilizational progress also indicate that the night in many areas of the world is no longer as dark as it should be, and that this new pollution is causing various functional imbalances in environmental systems, according to scientific studies in several fields. Among the main causes of this pollution is excessive lighting and various methods. It is often unscientific, as Ben Yahya says. Of the public lighting systems that are used in cities, human and industrial complexes, and on roads, we only use 10% of them, while the rest turns into a source of nuisance in various forms. An important part of it spreads directly into space, and another part is reflected on the floors. Industrial in turn spreads into the atmosphere
Keywords: light; pollution; sparkling lights